Meningkatkan Kinerja Karyawan melalui Employee Engagement, Lingkungan Kerja, dan Kepuasan Kerja - Alfira Nambo; Nur Aisyah; Muhammad Asgar; Raba Nathaniel; Nurhuda (BJRM (Bongaya Journal For Research in Management), 2025)
Human Resources (HR) in the company is very important because every company always strives to have quality HR, because without quality HR a company must have a mutually needy relationship. This study examines how much employee engagement, environment and job satisfaction have an influence on employee performance. The purpose of this study was to determine the effect of employee engagement, work environment and job satisfaction on employee performance of PT Bank Sinar Mas Palopo City Branch. This survey involved 30 employees who work at PT Bank Sinar Mas Palopo City Branch. In this study, the sampling technique used was saturated sampling technique, which is a sampling technique when all members of the population are used as samples. From this study it was found that employee engagement has a significant and negative effect on employee performance at PT Bank Sinar Mas Palopo Branch. The work environment has a significant and negative effect on employee performance at PT Bank Sinar Mas Palapo Branch and job satisfaction has a significant and negative effect on employee performance at PT Bank Sinar Mas Palapo Branch. The results of this study indicate that employee involvement can result in low company performance, work environment conditions that have a negative impact provide uncomfortable physical conditions and can lead to poor occupational safety and health and employees who have significant negative job satisfaction can have a detrimental impact on the company and this can damage the company's reputation.